Tumor markers and depression scores are predictive of non-suicidal self-injury behaviors among adolescents with depressive disorder: A retrospective study - Yi, Peng-cheng; Qin, Yan-hua; Zheng, Chun-mei; Ren, Ke-ming; Huang, Lei; Chen, Wei (Frontiers in Neuroscience, 2022)
Background Non-suicidal self-injury (NSSI) is an important risk factor for suicide in adolescents with depressive disorders; therefore, it is important to predict NSSI occurrence as early as possible. Disturbances in biological rhythms are characteristic manifestations of depressive disorders and can lead to immune dysfunction, leading to changes in tumor markers. This study aimed to produce anindexthat utilizes tumor markers to predict NSSI behaviors among adolescents with depressive disorders. Methods A total of 120 hospitalized adolescent patients with depressive disorders aged 14–24 years were included in this study. Participants were divided into NSSI and non-NSSI groups based on self-reports using the Ottawa Self-Injury Inventory. Demographics, tumor marker concentrations, other peripheral blood indices, Hamilton Depression Rating Scale (HDRS)scores, and Hamilton Anxiety Rating Scale (HAMA) scores were compared between the two groups. Logistic regression analysis was conducted to developajoint index, and areceiver operating characteristic(ROC)curve was created topredictNSSI behaviors among adolescents with depressive disorders. Results Compared with the non-NSSI group, the NSSI group had significantly higher insight, retardation, insomnia, hopelessness, psychiatric anxiety, total HDRS and HAMA scores,and significantly higher levels of cancer antigen125 (CA-125),cancer antigen19-9(CA19-9), and carcinoembryonic antigen (CEA). In addition, a joint index was developed by combining CA-125, CA19-9, CEA, HDRS total score, HAMA total score and age using multiple logistic regression to predict NSSI behaviors. The area under the curve was 0.831, with a sensitivity and specificity of 0.734 and 0.891, respectively. Conclusions A combination of depression score, tumor marker levels, and age can identify NSSI behaviors among adolescents with depressive disorders.